An Empirical Assessment of the Real Exchange Rate and Poverty in Nigeria - Omojimite, Ben. U; Oriavwote, Victor E (Asian Economic and Financial Review, 2012)
This paper investigated the influence of the real exchange rate on poverty within the framework of a dependent economy model. Using data covering 1980 to 2010, the result of a Vector Error Correction model (VECM) showed that the volatility of the real exchange rate has significant influence on the level of poverty in Nigeria. Thus, government policies that targets real exchange rate could play significant role in reducing the level of poverty in Nigeria, particularly if supported by basic institutions, such as those of human capital development.